PENTINGNYA JABATAN FUNGSIONAL DOSEN UNTUK MENINGKATKAN KARIER DOSEN - Lilis Setyowati; Zaky Machmuddah; Desy Herma Fauza (Universitas Serang Raya, 2018)
High number of lecturers with low functional occupation in Indonesia is the main issue of the article.Identifying what factors faced by lecturers in process of lecturer functional occupation proposal to improve career path of lecturer is the main aim of the article. Method used in the research is descriptive-qualitative, by gathering research articles about related problems and describing them.The research findings indicate that factors faced by lecturers in these matters are lack of insight of lecturers, leader support, Tri Dharma burdens, lack of socialization from institution and level of procedures of proposal. Practical implication of the research is giving insight to the lecturers about the importance of functional occupation of lecturers to support the career to contribute in institution development.Keyword: lecturer functional occupation, career path of lecturer, institution development